1986
DOI: 10.1002/j.1460-2075.1986.tb04505.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and transcriptional analysis of the start gene CDC25 of Saccharomyces cerevisiae

Abstract: To isolate the CDC25 gene of Saccharomyces cerevisiae we have transformed a cdc25‐1, trp1 strain with a yeast gene bank constructed in YRp7 vector, selecting trp+ clones able to grow at restrictive temperature. From several independent positive clones we have recovered a plasmid, called pDGEm‐1, that bears a 5‐kb genomic fragment and is able to give a full complementation of the cdc25‐1 mutation. The genomic sequence has been subcloned and a good complementation obtained with a 2‐kb fragment. Several stable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Adenylyl cyclase seems to be a primary target of systems that monitor the presence or absence of key nutritional compounds (Tatchell et al, 1985;Tripp et al, 1986;Boy-Marcotte et al, 1987;Mbonyi et al, 1988). The nutritional sensory systems whose existence is suggested by these observations do not appear to act directly on adenylyl cyclase but rather through intermediary proteins, three of which, encoded by the two RAS genes (Toda et at., 1985), and the CDC25 gene (Camonis et al, 1986;Martegani et al, 1986;Broek et al, 1987;Daniel et al, 1987), have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Adenylyl cyclase seems to be a primary target of systems that monitor the presence or absence of key nutritional compounds (Tatchell et al, 1985;Tripp et al, 1986;Boy-Marcotte et al, 1987;Mbonyi et al, 1988). The nutritional sensory systems whose existence is suggested by these observations do not appear to act directly on adenylyl cyclase but rather through intermediary proteins, three of which, encoded by the two RAS genes (Toda et at., 1985), and the CDC25 gene (Camonis et al, 1986;Martegani et al, 1986;Broek et al, 1987;Daniel et al, 1987), have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Nine dif ferent plasmids were isolated. Five of these nine con tained known genes: Three plasmids contained TPKl, which is one of the three genes that encode the catalytic subunits of the cAPK (Toda et al 1987a); one contained CDC25 itself (Camonis et al 1986;Martegani et al 1986b;Broek et al 1987;Robinson et al 1987); and the other contained CYRl, which encodes adenylyl cyclase (Kataoka et al 1985a). From restriction mapping and Southern hybridization data, the remaining four plasmids did not contain CDC25, RASl,RAS2,CYRl,TPKl,TPK2,or TPK3, all genes capable of suppressing cdc25^^ when they are carried on multicopy yeast plasmids.…”
mentioning
confidence: 99%
“…We have previously cloned the CDC25 gene (2,28), and we have used the cloned sequence to construct different isogenic strains in order to study the interactions between the CDC25 and RAS2 gene products. In (48).…”
mentioning
confidence: 99%